1979
DOI: 10.1182/blood.v53.2.264.264
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myelocytic leukemia (CML): failure to detect residual normal committed stem cells in vitro

Abstract: Granulocytic colonies grown in culture from marrow and peripheral blood from five patients with Ph1-positive CML and heterozygous at the G-6-PD locus were analyzed for G-6-PD in order to identify CFU-C that do not arise from the CML clone. The patients had both B and A enzymes in normal tissues, but their CML clones typed as B. Whereas about 50% of colonies from normal subjects heterozygous as the G-6-PD locus show type-A G-6-PD and 50% type B, only two of the 1308 colonies from the CML patients had type-A G-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…By the time of diagnosis, increased numbers of malignant precursors are detected among all haematopoietic lineages typically in association with a marked increase of both mature neutrophils and platelets, but not red cells (Faderl et al , 1999). In addition, it has been reported that an increased proliferation due to deregulation of CD34 + CML haematopoietic progenitor cells (HPC) could be responsible for both the pronounced expansion of leukaemic progenitors (Shtivelman et al , 1985; Eaves et al , 1986; Daley et al , 1990; Heisterkamp et al , 1990) and the excessive production of leukaemia‐colony forming units (CFU‐L) found in CML patients (Singer et al , 1979; Eaves et al , 1998). In turn, a decreased rate of apoptosis has also been reported to lead to the selective expansion of the BCR / ABL haematopoietic cell compartments in CML (Bedi et al , 1994; McGahon et al , 1994; Smetsers et al , 1994; Rowley et al , 1996).…”
mentioning
confidence: 99%
“…By the time of diagnosis, increased numbers of malignant precursors are detected among all haematopoietic lineages typically in association with a marked increase of both mature neutrophils and platelets, but not red cells (Faderl et al , 1999). In addition, it has been reported that an increased proliferation due to deregulation of CD34 + CML haematopoietic progenitor cells (HPC) could be responsible for both the pronounced expansion of leukaemic progenitors (Shtivelman et al , 1985; Eaves et al , 1986; Daley et al , 1990; Heisterkamp et al , 1990) and the excessive production of leukaemia‐colony forming units (CFU‐L) found in CML patients (Singer et al , 1979; Eaves et al , 1998). In turn, a decreased rate of apoptosis has also been reported to lead to the selective expansion of the BCR / ABL haematopoietic cell compartments in CML (Bedi et al , 1994; McGahon et al , 1994; Smetsers et al , 1994; Rowley et al , 1996).…”
mentioning
confidence: 99%
“…Genetic studies performed over 20 years ago demonstrated that the malignant clone in CML is a pluripotent hematopoietic stem cell, capable of differentiating into myeloid cells, monocytes, erythrocytes, and platelets (Bernstein et al, 1992;Douer et al, 1981;Fialkow et al, 1977;Koeffler et al, 1980;Martin et al, 1980;Singer et al, 1980;Singer et al, 1979). These studies identified that only single enzyme phenotypes of the X-linked G6PD isoenzyme were present in cells across the spectrum of hematopoietic lineages in women with CML who were heterozygous for this gene.…”
Section: Lessons From CML a Disorder Of The Hematopoietic Stem Cellmentioning
confidence: 99%
“…Although differentiation per se does not appear to be perturbed in the chronic phase of CML, the neoplastic (Ph + / BCR‐ABL + ) clone has usually already become dominant by the time of diagnosis. In addition, by this time, >95% of all of the intermediate myeloid progenitors detectable by conventional in vitro colony‐forming cell (CFC) assays are leukemic 2,3. Because these progenitors can continue to differentiate normally, they go on to produce all of the blood cells generated in patients with chronic phase disease with the exception of some of the lymphoid elements 4.…”
Section: Introductionmentioning
confidence: 99%